Drosophila tao Controls Mushroom Body Development and Ethanol-Stimulated Behavior through par-1. - King, I.; Tsai, L.T.; Pflanz, R.; Voigt, A.; Lee, S.; Jäckle, H.; Lu, B.; Heberlein, U. (Journal of Neuroscience, 2011)
In both mammalian and insect models of ethanol-induced behavior, low doses of ethanol stimulate locomotion. However, the mechanisms of the stimulant effects of ethanol on the CNS are mostly unknown. We have identified tao, encoding a serine-threonine kinase of the Ste20 family, as a gene necessary for ethanol-induced locomotor hyperactivity in Drosophila. Mutations in tao also affect behavioral responses to cocaine and nicotine, making flies resistant to the effects of both drugs. We show that tao function is required during the development of the adult nervous system and that tao mutations cause defects in the development of central brain structures, including the mushroom body. Silencing of a subset of mushroom body neurons is sufficient to reduce ethanol-induced hyperactivity, revealing the mushroom body as an important locus mediating the stimulant effects of ethanol. We also show that mutations in par-1 suppress both the mushroom body morphology and behavioral phenotypes of tao mutations and that the phosphorylation state of the microtubule-binding protein Tau can be altered by RNA interference knockdown of tao, suggesting that tao and par-1 act in a pathway to control microtubule dynamics during neural development.